Analisis Disiplin, Motivasi, dan Stres Kerja Terhadap Kinerja Karyawan UPW I Perumdam Samarinda - Ryan Fithan Maulidiansyah; Khairil Anwar; Mukhibatul Hikmah; Rosyid Nurrohman (Jurnal Digital Bisnis, Modal Manusia, Marketing, Entrepreneurship, Finance, & Strategi Bisnis (DImmensi), 2026)
This study is based on issues related to work discipline, work motivation, and work stress that may affect employee performance in maintaining the effectiveness of UPW 1 Perumdam Tirta Kencana Kota Samarinda as a regional public service enterprise. Previous studies have also reported inconsistent findings regarding the influence of these factors on employee performance. This research aims to analyze the effect of work discipline, work motivation, and work stress on employee performance at UPW 1 Perumdam Tirta Kencana Kota Samarinda. An explanatory quantitative approach was employed, with data collected through questionnaires, observations, and interviews. The sample consisted of 57 respondents using a saturated sampling technique. The results show that work discipline and work stress partially have a significant effect on employee performance, while work motivation partially does not have a significant effect. Simultaneously, work discipline, work motivation, and work stress significantly influence employee performance. These findings suggest that UPW 1 Perumdam Tirta Kencana Kota Samarinda should focus on managing work discipline and work stress through regular evaluations and consistent training. In addition, work motivation should continue to be addressed to support optimal employee performance